Household Socioeconomic Status and Nutritional Knowledge of Mothers of Stunted and Non-Stunted Toddlers in Tulang Bawang Tengah District - Tanjung, Rahmadani; Indriani, Yaktiworo; Ibnu, Muhammad (School of Nursing, Faculty of Medicine and Health Science, Universitas Lambung Mangkurat, 2025)
Stunting is one of the critical public health issues prioritized in Indonesia’s national development agenda. This study aims to analyze the differences in household socioeconomic status and maternal nutritional knowledge among mothers of stunted and non-stunted toddlers in Tulang Bawang Tengah District. The total sample comprised 42 mothers of toddlers, including 21 mothers of stunted toddlers and 21 mothers of non-stunted toddlers. Data were analyzed using quantitative descriptive statistics and the Mann–Whitney U test. The results showed that household income and maternal nutritional knowledge significantly contributed as indirect factors in the occurrence of stunting. There was a significant difference in household income between mothers of stunted and non-stunted toddlers. The level of nutritional knowledge among mothers of stunted toddlers was categorized as moderate. Therefore, it is necessary to enhance mothers’ curiosity and interest in learning more about food, nutrition, and signs of malnutrition in toddlers, in order to better prevent stunting.